Evaluation of rigid pavement damage using PCI and bina marga approaches (case study: Saketi–Malingping road, KM 17–27) - Irwan; Muhammad Oka Mahendra (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2026)
This study aims to evaluate the damage condition of the Saketi - Malingping road section (KM 17-KM 27) using two assessment approaches: the Pavement Condition Index (PCI) and the Bina Marga method. This road section is a strategic arterial road in Pandeglang Regency, Banten, which experiences high operational pressure and shows signs of surface distress. Data were collected through field surveys across 42 segments. The PCI analysis results show an average value of 99.99, indicating the road is in a